2019
DOI: 10.1002/nau.23973
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical administration of blebbistatin prevents cyclophosphamide‐induced toxicity of the urinary bladder in female Wistar rats

Abstract: Aims The main goal of our study was to investigate whether blebbistatin would prevent the cyclophosphamide (CYP)‐induced changes in cystometric and inflammatory parameters indicating the development of bladder inflammation and bladder overactivity. As the nature of CYP‐induced urotoxicity is inflammatory, we assume that agents presenting an anti‐inflammatory potential, such as blebbistatin, are worth special attention. Materials and Methods The experiments were carried out in female Wistar rats. Surgical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…21 In addition, after an acute CYP administration at a dose of 200 mg/kg Wróbe et al observed an increased urothelium thickness and bladder edema (measured by bladder permeability). 22 In the present study, the lamina propria showed dilated congested blood capillaries surrounded by perivascular cellular infiltration. This in a line with Auge et al who detected edema in the lamina propria and focal urothelial the urinary bladder injury after administration of CYP.…”
Section: Figure 3: (A) An Electron Microscope Photomicrograph Revealing the Ultrastructure Of The Urinary Bladder Of Control Group Rat Wisupporting
confidence: 54%
“…21 In addition, after an acute CYP administration at a dose of 200 mg/kg Wróbe et al observed an increased urothelium thickness and bladder edema (measured by bladder permeability). 22 In the present study, the lamina propria showed dilated congested blood capillaries surrounded by perivascular cellular infiltration. This in a line with Auge et al who detected edema in the lamina propria and focal urothelial the urinary bladder injury after administration of CYP.…”
Section: Figure 3: (A) An Electron Microscope Photomicrograph Revealing the Ultrastructure Of The Urinary Bladder Of Control Group Rat Wisupporting
confidence: 54%
“…Changes in the urinary bladders were less pronounced than described by other scientists in acute models of hemorrhagic cystitis induced by intraperitoneal injections of high-dose CPX. In this kind of CPX-induced bladder toxicity urothelial necrosis, vesical edema, increased urothelium thickness, erosion, ulceration, severe hemorrhage, inflammation, leukocyte infiltration, or even fibrosis were noticed [10,25,26].…”
Section: Discussionmentioning
confidence: 90%
“…Similar findings have been demonstrated in previous studies. [ 38,39 ] Data of the current study provided direct evidence of the potential role of oxidative stress in the development of hemorrhagic cystitis in CP‐treated rats and the antioxidant and anti‐inflammatory activities of ED. In this context, MDA and NO were increased and GSH, SOD, and GST were decreased in CP‐intoxicated rats, demonstrating an oxidative stress status.…”
Section: Discussionmentioning
confidence: 82%